Regional integration in Europe: The analysis of intra-Baltic economic cooperation - Vilpišauskas, Ramūnas (Politologija, 1999)
The article presents the analysis of the factors accounting for the dynamics of intra-Baltic economic cooperation. Namely, it addresses such questions: to what extent can the EU’s policy account for the development of intra-Baltic economic cooperation? Does the role of the EU explain the timing and the forms of the Baltic economic agreements, the successful conclusion of some cooperation schemes, for example, free trade and removal of non-tariff barriers, and the failure of others, namely, the customs union? Or does a satisfactory explanation of the cooperative dynamics among the Baltic States and instances of protectionism, or non-cooperation, need to include other factors, for example, sub-national interest groups or transnational actors? How do transition characteristics of the three countries influence the dynamics of regional cooperation? Finally, how further integration into the EU is likely to affect cooperation among the Baltic countries? The article reviews the existing literature on intra-Baltic cooperation and presents a different perspective based on liberal theories of international cooperation and concepts of political economy of regional integration. It presents a detailed theoretical framework on which the empirical analysis is built. The main arguments and propositions are summarized as follows. (1) The scope of intra-Baltic economic cooperation has been determined by the EU and by demands of domestic economic interest groups. Each factor can facilitate or obstruct sub-regional cooperation depending on the conditions specified. (2) The EU has acted as a supplier of sub-regional cooperation rules and indirect "supervisor" of sub-regional cooperation. The EU has also supplied financial assistance, although restricted, to administrative aspects and pre-accession measures. (3) The initial EU’s strategy of parallel and uniform treatment of the Baltic States and its emphasis on sub-regional cooperation as an informal precondition for the membership has gradually changed with the evolvement of enlargement politics and emphasis on individual achievements of applicant countries. The group approach towards the Baltic States has facilitated the intra-Baltic economic cooperation, while the differentiation proved to discourage it. (4) The issue of intra-Baltic economic cooperation has been high on their agenda since before and after the re-establishment of independence. However, after the establishment of relations with the EU it has become instrumental for advancing integration into the EU. After the EU’s decision to invite Estonia to start accession negotiations, the issue has become not so much how sub-regional cooperation affects integration into the EU, but how the latter might affect the former. Lack of resources, most of which have been mobilized for EU-oriented policies, has set further limits on intra-Baltic cooperation. (5) Therefore, the scope of intra-Baltic economic cooperation is influenced by how individual Baltic countries are situated in a gradual stage-like process of integration into the EU. Participation in different stages might discourage further sub-regional cooperation. (6) Intra-Baltic market integration has been limited largely to negative measures. When harmonization was agreed, it has been based on references to the EU rules. Sub-regional rules, common economic policies, and administrative structures have not been agreed upon because of coordination problems, high costs, and unclear potential benefits. (7) The role of interest groups has increased with the advance of political and economic transition, although to different extents, in each of the three countries. Depending on the expected gains and losses resulting from market integration, some economic groups are likely to oppose sub-regional economic cooperation while others are likely to support it. (8) The enterprises, using local resources and selling their goods domestically, domestically dominant (former state-owned) enterprises, have frequently demanded protection thereby negatively affecting intra-Baltic economic cooperation and market integration. Lack of resources for side payments to the disadvantaged groups has reduced the possibility of diminishing protectionist demands. (9) Protectionist demands are more likely to impede sub-regional cooperation when they exploit opportunities offered by channels to respective ministries or specialized agencies. The increasing complexity of regulation is likely to provide more opportunities for interest groups’ demands to be met by governmental institutions. Adoption (or the prospect of it) of EU rules and policies can be used as a bargaining tool by the domestic groups. (10) The internationalization, or informal economic integration, of the intra-Baltic markets by increasing trade flows and the presence of foreign investors has exerted indirect pressure on formal cooperation. Increasing internationalization of activities is likely to stimulate demands to further abolish the non-barriers to exchange and movement of factors. However, the size of the intra-Baltic market and the characteristics of intra-Baltic trade limiting the gains from economic cooperation reduce the incentive for strong demands. To test these propositions, the article discusses the dynamics of intra-Baltic economic cooperation in the area of market integration, trade relations in particular. It concludes with some forecasts concerning the likely developments of the two independent variables and their impact on intra-Baltic economic cooperation.